Stability-Preserving Slip Control of Articulated Heavy Vehicles Using Adaptive Longitudinal Slip Limits Derived from Phase Portraits - Vellingiri Ramasamy, Mathanesh (My University, 2025)
Ensuring the lateral stability of articulated heavy vehicles (AHVs) is critical for road safety, as they are susceptible to dangerous instability modes like jackknifing and trailer swing. Conventional stability control systems often rely on fixed slip thresholds, which may utilize higher slip limits than the proven safe limits under certain conditions, such as dynamic maneuvers involving high lateral accelerations. This thesis proposes an adaptive framework that determines safe longitudinal slip limits using phase portrait analysis. A computationally efficient, non-linear single-track model of a tractor-semitrailer combination was developed and validated against the high-fidelity simulation environment, Volvo Transport Model (VTM). The core of the methodology involves reducing the complex dynamics into a series of 2D phase planes for both the tractor and trailer units. Stability for each point on the phase plane is systematically classified using Largest Lyapunov Exponent (LLE), allowing for the automated generation of Safe Operating Envelopes (SOEs). This work establishes a robust methodology for generating state-dependent stability limits, laying the foundation for advanced control allocation strategies that can enhance the safety of AHVs by dynamically constraining actuator requests to remain within a safe region. The practical utility of this framework was demonstrated by designing and implementing two distinct control strategies in VTM. The first, an offline controller, utilizes the pre-computed SOEs as a multi-dimensional lookup table to adaptively constrain driver slip requests. The second, an online controller, was developed to generate these stability limits dynamically within the simulation, showcasing a pathway toward fully adaptive in-vehicle systems. The performance of both controllers confirms that the SOE-based approach can effectively prevent instability while maximizing the vehicle’s handling limit.
Keywords: articulated heavy vehicles; jack-knifing; trailer swing; adaptive longitudinal slip; phase portrait; safe operating envelope; control allocation